TINJAUAN ULANG TWO-CELL BOX GIRDER BETON PRATEGANG TERHADAP KAPASITAS DUKUNG BEBAN LALU LINTAS PADA PERENCANAAN PEMBANGUNAN FLY OVER SIMPANG SURABAYA KOTA BANDA ACEH - Munirul Hady; Taufiq Saidi; Muttaqin Hasan (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Syiah Kuala, 2017)
Abstract: Location of Simpang Surabaya is located in the city of Banda Aceh. At this intersection occurs meeting some of the main line to the city of Banda Aceh, causing traffic jams. This is the underlying construction of fly over Simpang Surabaya in 2016 using the two-cell cross-sectional as upper structure. The purpose of this study was to review the two-cell box girder in terms of safety (deflection and moment), and economically (volume superstructure box girder) by using the planning data flyover Simpang Surabaya. Fly over modeled as three-span continuous beam structure with a span configuration (45 + 50 + 45) m. Imposition of the box girder based on SNI 1725:2016. Planning fly over is based RSNI T-04-2005 and Manual 021 / BM / 2011. Increased traffic loads by increasing the burden Strip